2022 22nd IEEE International Symposium on Cluster, Cloud and Internet Computing (CCGrid) 2022
DOI: 10.1109/ccgrid54584.2022.00123
|View full text |Cite
|
Sign up to set email alerts
|

SparkFlow: Towards High-Performance Data Analytics for Spark-based Genome Analysis

Abstract: The recent advances in DNA sequencing technology triggered next-generation sequencing (NGS) research in full scale. Big Data (BD) is becoming the main driver in analyzing these large-scale bioinformatic data. However, this complicated process has become the system bottleneck, requiring an amalgamation of scalable approaches to deliver the needed performance and hide the deployment complexity. Utilizing cutting-edge scientific workflows can robustly address these challenges. This paper presents a Spark-based al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Early [6] work by scientists like Peter Shor and Lov Grover set the stage for quantum algorithms that could make problems like factorization and search much faster. Also, the creation of quantum error correction codes, especially the surface code, has been very helpful in fixing the fact that quantum information is naturally fragile.Companies like IBM, Google, and Rigetti Computing have [7] been working hard over the past few years to build and improve quantum computers. When Google's Sycamore processor reached quantum dominance, it was a major turning point in the field because it showed that a quantum computer could do some jobs better than traditional supercomputers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Early [6] work by scientists like Peter Shor and Lov Grover set the stage for quantum algorithms that could make problems like factorization and search much faster. Also, the creation of quantum error correction codes, especially the surface code, has been very helpful in fixing the fact that quantum information is naturally fragile.Companies like IBM, Google, and Rigetti Computing have [7] been working hard over the past few years to build and improve quantum computers. When Google's Sycamore processor reached quantum dominance, it was a major turning point in the field because it showed that a quantum computer could do some jobs better than traditional supercomputers.…”
Section: Review Of Literaturementioning
confidence: 99%